Benign schwannoma of the radial nerve mimicking cervical radicular pain (Faculty of Medicine Universitas Indonesia, 2012)
Radicular pain on the arm often referred to cervical disc problems. If cervical MRI is normal, then it is necessary to rule out peripheral nerve tumor. A 54-year old man presented with radicular pain in his left arm, investigated for cervical disc problems, with normal cervical MRI. Examination shows a positive Tinel's sign on the proximal part of his left arm. Focal MRI revealed a lobulated tumor in the radial nerve 1.5 cm in diameter. The patient was operated and the tumor was completely removed. Histopathology confirmed the diagnosis of schwannoma. (Med J Indones. 2012;21:118-20)